1
$\begingroup$

The method of moments estimator for AR processes can be had with the Yule-Walker equations. But how is it derived?

The equation for AR(1):

$$Y_t =aY_{t-1}+\epsilon_t$$

Where $\epsilon $ ~ $N(0,\sigma^2 )$.

So the moment conditions are $E(\epsilon)=0, E(\epsilon^2)=\sigma^2$

But the "standard" solution can't be used as $E(\epsilon)=E(Y_t-aY_{t-1})=0$ is true for any $a$.

$\endgroup$
1
$\begingroup$

I figured the answer:

Multiply the equation by $Y_{t-1}$

$Y_tY_{t-1}=aY_{t-1}Y_{t-1}+\epsilon_tY_{t-1}$

$E(Y_tY_{t-1})=E(aY_{t-1}Y_{t-1}+\epsilon_tY_{t-1})$

$E(Y_tY_{t-1})=aE(Y_{t-1}^2)$

$E(Y_tY_{t-1})/E(Y_{t-1})=a$

$E(Y_tY_{t-1})/E(Y_{t})=a$

And for $\sigma^2$:

$E((Y_t+aY_{t-1})^2)=\sigma^2$

$E(Y_t^2+a^2Y_{t-1}^2-2aY_tY_{t-1})=\sigma^2$

$E(Y_t^2+a^2Y_{t-1}^2-2aY_tY_{t-1})=\sigma^2$

$E(Y_t^2+a^2Y_{t-1}^2-2aY_{t-1}(aY_{t-1}+\epsilon_t))=\sigma^2$

$E(Y_t^2+a^2Y_{t-1}^2-2a^2Y_{t-1}^2)=\sigma^2$

$E(Y_t^2-a^2Y_{t-1}^2)=\sigma^2$

$E(Y_t^2)-a^2E(Y_{t-1}^2)=\sigma^2$

$(1-a^2)E(Y_{t}^2)=\sigma^2$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.